2019
DOI: 10.1016/j.compfluid.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

On the self-similarity of line segments in decaying homogeneous isotropic turbulence

Abstract: The self-similarity of a passive scalar in homogeneous isotropic decaying turbulence is investigated by the method of line segments (M. Gauding et al., Physics of Fluids 27.9 (2015): 095102). The analysis is based on a highly resolved direct numerical simulation of decaying turbulence. The method of line segments is used to perform a decomposition of the scalar field into smaller sub-units based on the extremal points of the scalar along a straight line. These sub-units (the so-called line segments) are param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 54 publications
(78 reference statements)
1
18
1
Order By: Relevance
“…Though it has been shown that statistical symmetries play a key role for the understanding of moment scalings in wall-bounded shear flows (see e.g. Oberlack et al 2015), we found no clear indication for its involvement for the temporal evolution of statistical quantities in the present flow when comparing to the DNS data of Gauding et al (2019). Still, as different initial conditions may have an influence via the statistical symmetries (see e.g.…”
Section: Symmetries Of the Instantaneous And Statistical Equationscontrasting
confidence: 76%
See 4 more Smart Citations
“…Though it has been shown that statistical symmetries play a key role for the understanding of moment scalings in wall-bounded shear flows (see e.g. Oberlack et al 2015), we found no clear indication for its involvement for the temporal evolution of statistical quantities in the present flow when comparing to the DNS data of Gauding et al (2019). Still, as different initial conditions may have an influence via the statistical symmetries (see e.g.…”
Section: Symmetries Of the Instantaneous And Statistical Equationscontrasting
confidence: 76%
“…5.1. Details of the direct numerical simulations We compare the derived theoretical solutions (4.12)-(4.15) and (4.24)-(4.27) based on the symmetry analysis against the highly resolved DNS results of decaying homogeneous isotropic turbulence, performed by Gauding et al (2015Gauding et al ( , 2017Gauding et al ( , 2019. While more details can be found in these references, we only briefly describe the details of their DNS code, which solved the incompressible Navier-Stokes equations (2.22) in a triply periodic cubic box with size 2π by a pseudo-spectral method.…”
Section: Validation Of Scaling Lawsmentioning
confidence: 99%
See 3 more Smart Citations